Natural inspired piperine-based ureas and amides as novel antitumor agents towards breast cancer. (1st January 2022) - Elimam, Diaaeldin M.; Elgazar, Abdullah A.; El-Senduny, Fardous F.; El-Domany, Ramadan A.; Badria, Farid A; Eldehna, Wagdy M.
Abstract: In this work, the natural piperine moiety was utilised to develop two sets of piperine-based amides (5a–i ) and ureas (8a–y ) as potential anticancer agents. The anticancer action was assessed against triple negative breast cancer (TNBC) MDA-MB-231, ovarian A2780CP and hepatocellular HepG2 cancer cell lines. In particular, 8q stood out as the most potent anti-proliferative analogue against TNBC MDA-MB-231 cells with IC50 equals 18.7 µM, which is better than that of piperine (IC50  = 47.8 µM) and 5-FU (IC50  = 38.5 µM). Furthermore, 8q was investigated for its possible mechanism of action in MDA-MB-231 cells via Annexin V-FITC apoptosis assay and cell cycle analysis. Moreover, an in-silico analysis has proposed VEGFR-2 as a probable enzymatic target for piperine-based derivatives, and then has explored the binding interactions within VEGFR-2 active site (PDB:4ASD). Finally, an in vitro VEGFR-2 inhibition assay was performed to validate the in silico findings, where 8q showed good VEGFR-2 inhibitory activity with IC50 = 231 nM.